Correction to: Separate Evaluation of the Effects of Hydroalcoholic Extracts of Eryngium Caucasicum Frautv. and Zataria Multiflora Boiss. on Gastric Ulcers in an Animal Model - Mahdi Jalahi; Mohammad Azadbakht; Jafar Akbari; Fereshteh Talebpuor; Fatemeh Akbari (Journal of Mazandaran University of Medical Sciences)
Mahdi Jalahi1, Mohammad Azadbakht2,3, Jafar Akbari4, Fereshteh Talebpuor5,6, Fatemeh Akbari7